2018
DOI: 10.3390/ijerph15081588
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sleep Disorders and Health Related Quality of Life—Results from the Georgia SOMNUS Study

Abstract: The extent to which sleep disorders are associated with impairment of health-related quality of life (HRQoL) is poorly described in the developing world. We investigated the prevalence and severity of various sleep disorders and their associations with HRQoL in an urban Georgian population. 395 volunteers (20–60 years) completed Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, STOP-Bang questionnaire, Insomnia Severity Index, Beck Depression Inventory-Short Form, and Short Form Health Survey (SF-12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 51 publications
11
36
1
1
Order By: Relevance
“…Notwithstanding, poor sleep quality is a common complaint among people with nocturia [6]. A study in the US reported that poor sleep quality can have a serious impact on the ability to function and daytime functioning, leading to impaired HRQOL [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, poor sleep quality is a common complaint among people with nocturia [6]. A study in the US reported that poor sleep quality can have a serious impact on the ability to function and daytime functioning, leading to impaired HRQOL [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies provide several socio-ecological explanations of sleep, which generally believe that sleep can be influenced by psychological and physiological factors, environment, financial status, and other social factors [16][17][18][19][20]. Anxiety could directly lead to poor sleep quality, and there is a strong association between depression symptoms and sleep disturbances [21].…”
Section: Introductionmentioning
confidence: 99%
“…The significant association between daytime dysfunction and mental health-related quality of life is not surprising as the daytime dysfunction subscale comprises of one question regarding fatigue and motivation and another question about trouble staying awake and daytime sleepiness, both of which may indicate depressive symptomatology. It is also well documented that individuals experiencing daytime dysfunction as a result of sleepiness are more likely to present depressive symptoms [18,22,33,46]. One cause of daytime dysfunction is insufficient sleep, and participants in our study averaged 5.8 h of sleep a night, more than an hour short of the 7 to 9 h recommended for optimal health [47].…”
Section: Discussionmentioning
confidence: 69%
“…Unlike PSG, it allows for prolonged continuous periods of sleep evaluation in the subject’s natural work and sleep environments without being labor-intensive [15,16]. A number of studies have reported on the association between subjectively assessed parameters of sleep and health-related quality of life [17,18,19,20,21,22,23,24,25], while fewer have examined their relationship with objective measurements of sleep [26]. Given the difference in cost, accessibility, and ease of administration, it is understandable that subjective assessments of sleep are often opted for over objective measurements, however, the extant literature has demonstrated inconsistencies between subjectively and objectively measured sleep [27,28,29], and therefore studies that include both methods are warranted.…”
Section: Introductionmentioning
confidence: 99%